An Evaluation of Stock Fair Value Using Fundamental and Technical Analysis with DDM and PER Approaches - Fajri, Mega Barokatul; Hidayatul Lailiyah, Elliv; Rafikah Zulyanti, Noer; Syah, Imran; D. Oktanti, Ellen (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
For an investor, it is very important to conduct a stock valuation before making a transaction because stock valuation is a form of rationalization for an investor in making investment decisions. The purpose of this study itself is to evaluate the intrinsic value of PT Indofood Sukses Makmur Tbk (INDF) shares using two approaches, namely fundamental analysis and technical analysis. In fundamental analysis, economic, industry, and company analyses are carried out. The fundamental analysis methods used are the dividend discount model (DDM) and price-earnings ratio (PER), while technical analysis is carried out using moving average indicators and the relative strength index. The results of this study indicate a relatively strong trend in the Indonesian economy and a fairly strong resilience in the face of trade wars. In terms of industry, INDF continues to experience growth both in terms of sales and in terms of net profit. And the results of calculations using the DDM and PER methods show that the INDF share price has an intrinsic value that is much higher than the value of shares in the market, so it can be concluded that INDF shares are classified as undervalued. And in terms of technical analysis, the intrinsic value of INDF shares is in the price range of IDR 6,500 to IDR 7,250. From this analysis, it indicates that the current stock value in the market is low and still has the potential to be purchased because of its higher intrinsic value.